Injectable shear-thinning hydrogels for delivering osteogenic and angiogenic cells and growth factors - (:unkn) unknown (ROYAL SOC CHEMISTRY, 2018)
Bone nonunion may occur when the fracture is unstable, or blood supply is impeded. To provide an effective treatment for the healing of nonunion defects, we introduce an injectable osteogenic hydrogel that can deliver cells and vasculogenic growth factors. We used a silicate-based shear-thinning hydrogel (STH) to engineer an injectable scaffold and incorporated polycaprolactone (PCL) nanoparticles that entrap and release vasculogenic growth factors in a controlled manner. By adjusting the solid composition of gelatin and silicate nanoplatelets in the STH, we defined optimal conditions that enable injection of STHs, which can deliver cells and growth factors. Different types of STHs could be simultaneously injected into 3D constructs through a single extrusion head composed of multiple syringes and needles, while maintaining their engineered structure in a continuous manner. The injected STHs were also capable of filling any irregularly shaped defects in bone. Osteogenic cells and endothelial cells were encapsulated in STHs with and without vasculogenic growth factors, respectively, and when co-cultured, their growth and differentiation were significantly enhanced compared to cells grown in monoculture. This study introduces an initial step of developing a new platform of shape-tunable materials with controlled release of angiogenic growth factors by utilizing PCL nanoparticles.
Keywords: MESENCHYMAL STEM-CELLS; LOADED PLGA NANOPARTICLES; IN-VITRO; ENGINEERING STRATEGIES; AVASCULAR NECROSIS; CONTROLLED-RELEASE; ENDOTHELIAL-CELLS; BONE REPAIR; DIFFERENTIATION; VASCULARIZATION